Analyse De L’impact Du Changement De La Couverture Végétale Sur La Pluie Et La Température De Surface Au Sénégal - Diba, Ibrahima; Camara, Moctar (European Scientific Journal, ESJ, 2017)
This work aims at examining the potential impacts of vegetation change (reforestation) of the Sahel-Sahara interface on the intra-seasonal and interannual variability of the rainfall and surface temperature over Senegal using the RegCM4 model. Two runs were performed from 1990 to 2009 with a spatial resolution of 50 km (0.44 °): the standard version of the RegCM4 model (control version) and the reforested one (named RegCM4_REFORESTATION). The impact of the reforestation is to decrease the surface temperature over Senegal in summer (JJAS). This decrease could be partly due to a decrease of the sensible heat flux over the southern and central Senegal and a strong increase of the latent heat flux. The reforestation also tends to increase the rainfall over the whole country and particularly in the Southwest. This rainfall increase which can also create an evaporative cooling, is consistent with the decrease of the surface temperature. The analysis of the annual cycle over three domains of Senegal shows that the reforestation tends to strengthen the low-levels humidity of the atmosphere from January to December especially during the summer period in the North and in the center of the country. The surface temperature presents two maxima in April-May and October-November and a minimum during the summer. The reforestation has a cooling impact during the whole year (particularly in the summer) and over the center and the northern part of Senegal. At the interannual timescale, the reforestation modifies significantly the rainfall by generally increasing it. However, there are years in which this trend is not respected and this translates into a weak correlation coefficient in the South of the country. This rainfall increase may translates into extreme hydroclimatic events such as floods. This work can be considered as a support for the Senegalese policymakers for the better planning of the management of adverse potential effects (such as floods, drought, heat waves, etc) of the Sahel-Sahara greening effort.